2005
DOI: 10.1242/jcs.02369
|View full text |Cite
|
Sign up to set email alerts
|

Centaurin-α1 interacts directly with kinesin motor protein KIF13B

Abstract: Centaurin-α1 is a phosphatidylinositol 3,4,5-trisphosphate binding protein as well as a GTPase activating protein (GAP) for the ADP-ribosylation factor (ARF) family of small GTPases. To further understand its cellular function, we screened a rat brain cDNA library using centaurin-α1 as bait to identify centaurin-α1 interacting proteins. The yeast two-hybrid screen identified a novel kinesin motor protein as a centaurin-α1 binding partner. The motor protein, termed KIF13B, encoded by a single ∼9.5-kb transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
73
2
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(80 citation statements)
references
References 58 publications
4
73
2
1
Order By: Relevance
“…The observation that Arf GAPs, such as centaurin ␣1 and ArfGEFs, such as EFA6 and ARNO are potentially regulated by PtdIns(3,4,5)P 3 , and found in dendritic and synaptic regions, lends support to the hypothesis that PI 3-kinase coordinately regulates GEFs and GAPs that control the Arf pathways required for dendritic development. In addition, centaurin ␣1 has multiple identified binding partners in addition to PtdIns(3,4,5)P 3 , including protein kinases and cytoskeletal proteins, which could provide input to centaurin ␣1 regulation from a variety of signaling pathways (Dubois et al, 2001;Dubois et al, 2003;Zemlickova et al, 2003;Thacker et al, 2004;Venkateswarlu et al, 2005;Striker et al, 2006). In turn, centaurin ␣1 may also provide cross-talk to other signaling pathways such as the Ras-MAP kinase pathway, which was shown to be diminished by reducing centaurin ␣1 expression (Hayashi et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observation that Arf GAPs, such as centaurin ␣1 and ArfGEFs, such as EFA6 and ARNO are potentially regulated by PtdIns(3,4,5)P 3 , and found in dendritic and synaptic regions, lends support to the hypothesis that PI 3-kinase coordinately regulates GEFs and GAPs that control the Arf pathways required for dendritic development. In addition, centaurin ␣1 has multiple identified binding partners in addition to PtdIns(3,4,5)P 3 , including protein kinases and cytoskeletal proteins, which could provide input to centaurin ␣1 regulation from a variety of signaling pathways (Dubois et al, 2001;Dubois et al, 2003;Zemlickova et al, 2003;Thacker et al, 2004;Venkateswarlu et al, 2005;Striker et al, 2006). In turn, centaurin ␣1 may also provide cross-talk to other signaling pathways such as the Ras-MAP kinase pathway, which was shown to be diminished by reducing centaurin ␣1 expression (Hayashi et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Human Flag-centaurin ␣1 constructs were kindly provided by Kanamarlapudi Venkateswarlu (Venkateswarlu et al, 2005) and Muahamed Hawadle (Neural Development Unit, UCL Institute of Child Health, UK). eGFP vectors were obtained from Clontech.…”
Section: Plasmidsmentioning
confidence: 99%
“…Centaurin-␣ 1 (also known as PIP3BP/p42 IP4 ) was originally identified as a PIP 3 or its inositol head group, inositol 1,3,4,5-tetrakisphosphate (IP 4 ), binding protein (Hammonds-Odie et al, 1996;Stricker et al, 1997;Tanaka et al, 1999). This protein acts as a PIP 3 -dependent ARF6 GAP that regulates GPCR internalisation and actin reorganisation (Lawrence et al, 2005;Venkateswarlu et al, 1999a;Venkateswarlu et al, 2004;Venkateswarlu et al, 2005). Centaurin-␣ 1 contains an Nterminal ARF GAP domain and two adjacent PH domains [one in the middle (N-PH) and the other at the C terminus (C-PH)] that are required for binding to PIP 3 (Venkateswarlu et al, 1999a).…”
Section: Introductionmentioning
confidence: 99%
“…In mammalian (neuronal) cells, p42 IP4 regulates the actin cytoskeleton via ARFGAP-dependent and -independent mechanisms (Thacker et al 2004;Venkateswarlu et al 2004). It is involved in various signaling cascades, such as activation of the ERK mitogen-activated protein kinase cascade (Hayashi et al 2006), ARF6 signaling pathway (Venkateswarlu et al 2005) or transcription factor AP-1 activation cascade (Chanda et al 2003). In addition, p42 IP4 seems to be involved in neuronal diseases, such as Alzheimer disease, since we have found that besides the known intracellular localization, p42…”
mentioning
confidence: 95%
“…p42 IP4 can shuttle between cytosol, nucleus and plasma membrane, depending on the cell stimulation situation . Several interaction partners of p42 IP4 have been identified, such as casein kinase I (Dubois et al 2001(Dubois et al , 2002, nucleolin , protein kinase C , several ARFs (Thacker et al 2004;Venkateswarlu et al 2004) GAKIN (Venkateswarlu et al 2005;Horiguchi et al 2006), the peptidase nardilysin (Stricker et al 2006) or F-actin (Thacker et al 2004). It has been shown that p42 IP4 is a component of the neuronal phosphatidyl inositol 3-kinase cascade and is involved in dendritic differentiation/synaptic plasticity and/or transport of PtdIns(3,4,5)P 3 -containing vesicles along axons to regulate neuronal cell polarity (Horiguchi et al 2006;Moore et al 2007).…”
mentioning
confidence: 99%